Literature review of climate resilient agri-food systems in the coastal zone of Bangladesh - Ali, A M M Mostafa; Rahman, Md. Mostafizur; Rashid, Mohammad Abdur; Hossain, Bhuiya Md. Tamim Al; Haque, Md. Zahidul; Sikder, Abdul Halim Farhad; Saha, Champa Rani; JulkerNaem, A. S. M. (CGIAR Initiative on Asian Mega-Deltas, 2024)
Agriculture in Bangladesh is influenced by climate, its seasonal characteristics and different climatic variables such as temperature, rainfall, humidity, day length, etc. Consequently, climate change as indicated by a rising trend in average temperature and volatility of the precipitation regime will affect agriculture to an extent. On average, weather-related natural hazards such as flood and drought as well as salinity already affect respectively 34%, 15% and 4% of total households affected by all hazards and associated with 23%, 6% and 3% respectively of total damage and losses occurring in Bangladesh during 2009-14. Among the sectors, crop cultivation experienced the highest damage and loss (around 36%). The frequency and severity of all these hazards may increase over time as climate change unfolds and with it, the prospects for agriculture in general are also going to be uncertain possibly jeopardizing food security in the country. For future food security, it is absolutely necessary to understand how Bangladesh’s agriculture can advance in the future under climate change.